Inosine monophosphate dehydrogenase 2 (IMPDH2) modulates response to therapy and chemo-resistance in triple negative breast cancer - Tatiane da Silva Fernandes; Bryan M. Gillard; Tao Dai; Jeffrey C. Martin; Kanita A. Chaudhry; Scott M. Dugas; Alyssa A. Fisher; Pia Sharma; RongRong Wu; Kristopher M. Attwood; Subhamoy Dasgupta; Kazuaki Takabe; et al. (Scientific Reports)
Abstract Triple negative breast cancer (TNBC) is one of the deadliest subtypes of breast cancer, whose high frequency of relapse is often due to resistance to chemotherapy. Here, we identify inosine monophosphate dehydrogenase 2 (IMPDH2) as a contributor to doxorubicin resistance, in multiple TNBC models. Analysis of publicly available datasets reveals elevated IMPDH2 expression to associate with worse overall TNBC prognosis in the clinic, including lower recurrence-free survival post adjuvant/neoadjuvant therapy. Importantly, both genetic depletion and pharmacological inhibition of IMPDH2 leads to reduction of pro-tumorigenic phenotypes in multiple doxorubicin-resistant TNBC models, both in vitro and in vivo. Overall, we propose IMPDH2 as a novel vulnerability that could be leveraged therapeutically to suppress and/or prevent the growth of chemo-resistant lesions.